Produksi Blok Silinder Aluminium Cor Diameter 54,5 mm x Langkah 59 mm Kapasitas 2 Unit/Jam (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
. The manufacturer's discontinuation of original spare parts for the 149 cm3 two-stroke cylinder block has had a significant impact, resulting in a shortage of products sought by consumers, creating a market gap for local manufacturers to produce spare parts with equivalent and competitive quality. The production objective is to obtain an ADC12 cast aluminum cylinder block with a diameter of 54.5 mm x a stroke of 59 mm. The production method includes: a series of systematic steps of 3D scanning of the cylinder block for geometric accuracy, making a Resin Sand Casting (RSC) mold whose size has been increased due to the shrinkage percentage ADC12-Machining-Pattern removal slope, making a core for the hollow part from RSC material, a melting process using an LPG furnace in parallel stages using 2 RSC molds, natural cooling for about 60 minutes, cutting the casting bowl channel and cutting the riser, T6 heat treatment, and quality and dimensional inspection. The production results are in the form of an ADC12 cast aluminum cylinder block with a diameter of 54.5 mm x stroke of 59 mm, the tensile strength after heat treatment is around 300 MPa, the total production cost is IDR 375,000/unit, and the process duration is 30 minutes/unit which implies that the need for a cylinder block volume of 149 cm3 for two-stroke motorcycles (takt) can be met, so that this type of motorcycle can be used again.